Menumbuhkan kecintaan terhadap Allah dan Rasul melalui metode bercerita pada pembelajaran PAI di Kelas 1 Sekolah Dasar - Sholihah, Nur Hidayatus (Maliki Interdisciplinary Journal, 2024)
Childhood is an important period for instilling moral and religious values ​​in children. One of the values ​​that must be instilled is love for Allah and the Messenger. Islamic Religious Education (PAI) in Elementary Schools (SD) has an important role in fostering this love. This research aims to determine the effectiveness of the storytelling method in fostering love for Allah and the Messenger in grade 1 elementary school students. The research method used is qualitative research with a case study design. Data was collected through observation, interviews and document analysis. The results of the research show that the storytelling method is effective in fostering love for Allah and the Messenger in grade 1 elementary school students. This is evidenced by the increase in students' interest and motivation in learning, the increase in students' understanding of PAI material, and the increase in students' love for Allah and the Messenger. The storytelling method has several advantages, namely interesting and fun, easy to understand, helps students to visualize abstract concepts, improves students' memory, and increases students' creativity. However, the storytelling method also has several disadvantages, namely that it takes a long time, requires special skills, and is difficult to measure.